RNA modification: a promising code to unravel the puzzle of autoimmune diseases and CD4+ T cell differentiation - Yu, Hui; Ma, Zhanchuan; Su, Sensen; Xu, Zheng; Yi, Huanfa (Frontiers in Immunology, 2025)
Dynamic changes in various forms of RNA modification are critical to the functional homeostasis of the immune system and the pathophysiology of autoimmune diseases. RNA modification-related proteins play an essential role in these processes. At present, the research methods of RNA modification in autoimmune diseases are mainly to detect the expression changes of RNA modification-related proteins in tissues or cells, but there is a lack of explorations of target RNAs and in-depth mechanisms. Considering the important role of CD4+ T cell dysfunction in the pathogenesis and progression of autoimmune diseases, the regulatory effect of abnormal RNA modification on CD4+ T cells deserves attention, which will provide a perspective for further exploring the mechanism of RNA modification in autoimmune diseases. In this Review, we discuss the abnormal RNA modification changes in patients with autoimmune diseases and highlight the effects of these abnormal changes on CD4+ T cells.